Production of human liver prolidase by Saccharomyces cerevisiae as host cells - WANG Shu-hao; LIU Min; CHI Mu-gen; WANG Qing-ding; SUN Man-ji (Acta Pharmacologica Sinica, 2016)
AIM: To clone and express the recombinant human liver prolidase in yeast and explore the activities of both dipeptidase and organophosphoric acid anhydrolase (OPAA). METHODS: The cDNA encoding human liver prolidase derived from healthy adult liver was cloned into the pYES2, an expression vector of S cerevisiae, and then transformed into S cerevisiae INVSc1 by electroporation. The transformant with the highest enzymatic activity was induced by galactose for expression. The optimal induction conditions (temperature, induction time, and the initial amount of inoculation cells) were estimated by orthogonal experimental design. The recombinant prolidase and OPAA activities were assayed by spectrocolorimetric methods. RESULTS: The recombinant enzyme catalyzed the hydrolysis of organophosphorous compound soman as well as the hydrolysis of dipeptide Gly-Pro. Under the optimal induction conditions (20 h, 25 degree, initial OD(600)=0.4), the maximum activities of prolidase and OPAA came to 226.5 and 578 micromol.min(-1).g(-1) protein in cell lysate supernatants, respectively. SDS-PAGE of the recombinant enzyme in disrupted cell supernatants showed a molecular weight of 56 kDa. Intensity scanning of the SDS-PAGE gel revealed that the enzyme accounted for 3.16 % of the total protein in the supernatant. One liter incubation medium produced 7 g of wet yeast cell containing 4.56 mg of the recombination protein. CONCLUSION: The recombinant human liver prolidase produced by yeast cell (S cerevisiae) exhibited both dipeptidase and OPAA activities.